Digital Transformation and Inclusive Economic Development in Indonesia: Human Development as a Conditional Regional Factor - Syamsul Huda (Cita Konsultindo Research Center, 2026)
This article critically examines how digital transformation is associated with inclusive economic growth across Indonesian provinces and whether human development conditions that relationship. The study uses provincial panel data for 2017 to 2023 and applies panel regression with an interaction specification. Inclusive growth is represented by the income distribution and poverty reduction dimension of the inclusive economic development index, while digitalization is proxied by the information and communication technology development index. The empirical pattern suggests that digitalization is positively related to inclusive growth. However, the interaction between digitalization and human development is negative and statistically meaningful, indicating that higher human development does not automatically intensify the inclusive benefits of technology. A sub sample reading reveals different regional dynamics. Digitalization appears to expand economic access in provinces with lower human development, whereas in more developed provinces it may concentrate gains among workers and firms with stronger digital capability. The article argues that digitalization should not be treated as a socially neutral development instrument. Its inclusive value depends on the distribution of skills, infrastructure, labor protection, and regional absorptive capacity. Policy responses therefore need to be differentiated, with basic access and literacy prioritized in lagging regions and advanced digital skills, labor transition support, and platform regulation strengthened in more developed regions.